Determinants and convergence of CO₂ emissions in the developing economies - Jalil, Siti Ayu (2013)
The year 1991 saw developing countries categorized by the UNFCCC as “Non-Annex I Countries” which represent the countries held responsible for the rapid growth of the world‟s CO2 emissions. The commitment to meet social and economic development goals and the pressures of their huge size of the economy, high energy consumption, large population and exploding growth rates have intensified the growth of carbon emissions in these countries. In this study, a range of factors from socio-economic to institutional aspects, are selected for analysis, which based on theory and previous empirical studies are identified as the potential determinants of carbon emissions. Thus, the first and second objectives of this research are to determine the factors affecting the growth of CO2 emissions in the selected 126 developing countries for the period 1971-2009. The investigation will include analysis based on regions i.e. Africa, Latin America and the Caribbean, Middle East and North Africa and Asia and the Pacific. The study analyzes a dynamic panel model utilizing the Generalized Method of Moments (GMM) technique. The results on socio-economic factors found that GDP per capita, energy consumption from fossil fuels (EFF), energy usage (EUS), inflows of foreign direct investment (FDI), urbanization (URB), industrial production (IND), agriculture production (AGR) and level of education (EDU) have shown a highly significant impact on the growth of carbon emissions in the entire developing region. All these factors indicated a highly significant positive relationship with per capita CO2 emissions except for urbanization which had a negative relationship. In all four regions studied, GDP per capita and EFF have been illustrated to be the most significant factors affecting growth of carbon emissions. The analysis on institutional aspects is focused on the Kyoto Protocol, political stability, legal structure and property rights, corruption and freedom of trade on CO2 emissions. The results showed that the Kyoto commitment (Kcom) to be the sole indicator with a negative and statistically significant relationship which can be interpreted to mean that signing and ratifying the Protocol is not an indication of intention to reduce carbon emission. The four institutional factors analyzed did not portray any significant relationships with the growth of CO2 emissions in the region. The final objective was to examine the existence of convergence of the per capita CO2 emissions which was crucial to come up with appropriate suggestions for policy implementation and the implications of CO2 emissions in the region. Based on the Phillips and Sul‟s (2007) log-t model, it is seen that per capita CO2 emission levels do converge for the whole developing region. However, on a regional basis, only Latin America and the Caribbean exhibited convergence in CO2 per capita while the other regions showed a divergence. Nevertheless the three regions which displayed divergence portrayed certain characteristics of club convergences. Firstly, only a small number of club convergences were identified for each region. Secondly, a majority of these countries were in the divergence category. Finally, each of the club convergences was found to be in congruence with income classifications. In other words high income countries form one club while low income countries form another. The discussion on policy implications was focused on existing policies that could be appropriately implemented to control increases in CO2 emissions. The evaluation was based on the findings of the determinants in each region and from the perspective of the club convergences identified. The findings on all regions indicate that GDP per capita and energy consumption from fossil fuel (EFF) have significant effects on carbon emissions. However, energy consumption (EUS) per se was found to significant only for the LAC and the Asia-Pacific regions. A uniform policy may thus not be suitable to control the problem of emissions in these regions. A better method would be to consider each club of countries whose emissions are converging to similar levels. According to Burnett (2013) understanding different clubs of countries whose emissions are converging at similar levels will help policymakers to develop differentiated policies. Since these nations are highly dependent on fossil fuels, it is best to implement an array of energy policies that may have direct or indirect effects on reducing CO2 emissions (Dinica, 2002). Thus, it is suggested that a good starting point for these nations may be to focus on energy conservation policies. Energy conservation policies could be in the form of energy savings and introduction of alternative sources of energy through participation in CDM projects to promote clean energy development such as hydroelectric, geothermal, nuclear, biomass, wind and solar. Other policies like deforestation, strengthening regulations and environmental laws together with strict enforcement can be implemented in each region or country but may depend on their economic circumstances and societal awareness of issues related to environmental problems. This study attempts to meticulously analyze the growth of CO2 emissions in 126 developing economies that cover one third of the countries in the world. As future large emitters these countries‟ efforts to cut CO2 emissions will be vital. The researcher found that there has not been any comprehensive analysis of CO2 emissions involving developing economies on such a big scale. Application of a dynamic panel model such as the generalized method of moments (GMM) econometric technique is still relatively new for a scope of study of this size. Further, convergence analysis of per capita CO2 emissions is crucial to guide policymakers‟ projection models when preparing climate change policy proposals. As such it is hoped that any information gained through this study will be helpful for policymakers, specifically the scenarios on carbon emissions from the perspective of developing countries which may help create awareness that are useful in combating the problem of climate change in the future.